PENGELOLAAN PENGIMBASAN SEKOLAH RUJUKAN DI SMP NEGERI 3 KABUPATEN KETAPANG - Malinda, Sy. Sari; Chiar, M; Aswandi, Aswandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this study is to describe the planning, organizing, implementing, and supervising the impact of the impact schools on the reference schools in SMP Negeri 3 Ketapang. The form of this research is a case study research with a qualitative approach. The subjects of this study were three heads of 56 Public Schools in Ketapang, 56 years old, male, 51-year-old deputy head of curriculum in the field of women, and 50-year-old head of the scoring team female. Data collection methods by interview, documentation, and observation. Data analysis uses interactive data analysis namely data reduction, data display, and verifications. Test the validity of the data with four criteria used, namely the test of credibility, transferability, dependability, and confirmability.The main findings of this study indicate as follows: (1) the planning of scoring made the results of the decision of the meeting between the principal, deputy headmaster in the field of curriculum, and the head of the scoring team to determine the referral school scoring program for impact schools (2) the organizing of the scoring was carried out by setting out a divide work into smaller personnel tasks, assigning those personnel duties to those who are within their abilities. (3) the implementation of scoping starts from training workshops on various aspects of SNP or others to the impact school, mentoring to the impact school, reflection and follow-up of the scoring assistance, workshop for the preparation and development of the scoring instrument, the formation and supply of the monitoring team for the evaluation of scoring, and implementation monitoring evaluation of scoring, and (4) supervision of scoring is carried out by the principal as the full person in charge of scoring, the secretary of the Ketapang district education office and the curriculum head of the Ketapang district education department.The conclusions of planning, organizing, implementing, supervising referral school scaling are in accordance with the technical guidelines for developing referral school strategies and the implications of the stages of managing scoring are in accordance with management principles.Keywords: Management of Assessment, Reference Schools